2005
DOI: 10.1111/j.1751-1097.2005.tb01542.x
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of Singlet Oxygen Dose from Photosensitizer Fluorescence and Photobleaching During mTHPC Photodynamic Therapy of MLL Cells

Abstract: Predicting the therapeutic outcome of photodynamic therapy (PDT) requires knowledge of the amount of cytoxic species generated. An implicit approach to assessing PDT efficacy has been proposed where changes in photosensitizer (PS) fluorescence during treatment are used to predict treatment outcome. To investigate this, in vitro experiments were performed in which Mat‐LyLu cells were incubated in meta‐tetra(hydroxyphenyl)chlorin (mTHPC) and then irradiated with 652 nm light. PS concentration, fluence rate and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 52 publications
4
48
0
Order By: Relevance
“…The combination of laser light and PS obviously effects bacterial life of deeper biofilm layers to a greater extend than treatment with CHX. Another reason for the modest increase in bacterial reduction might be caused by photobleaching of safranine O. Photobleaching refers to an irreversible destruction of PSs during illumination with light and has been measured for a vast variety of dyes [50,51]. Throughout the present study there were no further examinations performed which observed the photobleaching of safranine O during photodynamic treatment.…”
Section: Discussionmentioning
confidence: 81%
“…The combination of laser light and PS obviously effects bacterial life of deeper biofilm layers to a greater extend than treatment with CHX. Another reason for the modest increase in bacterial reduction might be caused by photobleaching of safranine O. Photobleaching refers to an irreversible destruction of PSs during illumination with light and has been measured for a vast variety of dyes [50,51]. Throughout the present study there were no further examinations performed which observed the photobleaching of safranine O during photodynamic treatment.…”
Section: Discussionmentioning
confidence: 81%
“…Dysart et al (32) performed PDT on cells sensitized with mTHPC and observed oxygen-dependent photobleaching with a faster rate of bleaching under air-saturated conditions. In a subsequent study (33) the same authors examined the relationship between mTHPC photobleaching and cell survival in response to PDT and reported not only a close correlation for dose metric models based on '02-mediated photobleaching and cell survival, but also a dependence of mTHPC bleaching rate on sensitizer incubation concentration.…”
Section: Kand[a] Photofrin's Approximately Two-fold Lower K/k[a]mentioning
confidence: 94%
“…This model relies on the assumption that PDT-induced singlet oxygen causes tissue damage as well as photodegradation of the photosensitiser. The usefulness of an implicit dosimetry model has been confirmed in pre-clinical models [24,25] as well as for human skin-PDT [26,27] where a rapid photobleaching has been shown to correlate with improved treatment outcome. Speculatively, the PpIXspecific photobleaching kinetics might be employed for early treatment prognosis and to assure the application of a sufficient light dose in order to improve treatment efficacy [28].…”
Section: Introductionmentioning
confidence: 92%